دراسة الخواص الميكانيكية لمنتج من مادة الفولاذ واطئ التسبيك - عبود عباسستار (University of Thi-Qar Journal of Science, 2019)
Mechanical properties have been determined for a low alloy steel sample, which according to it determined acceptance of the sample product comparing with stander characteristics . Purity test have been a chivied by the DIN-characteristic (DIN-5060), which depend on the industrial way (ESR), the low value obtained equal to (K1=5.1) whenever high value obtained equal to (K1=8). As well as the tensile ultimate value (1116-1332 N/mm2) and yield point has been reached which are included with slandered measurement. Also the impact test have been investigated, the results arranged between 63-108 Joule. Also the hardness test has been done under the standard measurement.